Biodegradation measurements confirm the predictive value of the O:C‐ratio for biochar recalcitrance. Issue 4 (3rd July 2014) - Bai, Mo; Wilske, Burkhard; Buegger, Franz; Bruun, Esben Wilson; Bach, Martin; Frede, Hans‐Georg; Breuer, Lutz
Abstract Suitable predictors of degradability are sought to support the identification of biochars with large potential to increase C sequestration in soils. We determined the biodegradation of 9 chars from hydrothermal carbonization and pyrolysis in two agricultural soils. The 200‐ and 115‐day degradation correlated strongly with the O:C‐ and slightly with the H:C‐atomic ratio of 9 and 14 biochars, respectively. Highest temperature treatment and ash content did not show similar correlations.